Manajemen Sistem Informasi Pendaftaran Siswa Baru Pada Sma Pendawa Pebayuran Berbasis Website - Prabowo, Wahyudi; Komara, Erwan (Jurnal Keilmuan Teknologi Informasi dan Ilmu Manajemen (Justifi), 2021)
In the current millennial era, information technology is advancing rapidly and in diversity. The advent of the internet will greatly facilitate learning new things without space and time. Computers are equipment designed to meet human needs. In this case, the admission of new students is carried out on the problems carried out by each educational institution / institution in accepting prospective students in the new school year, where so far there are still institutions that have a manual registration system starting from registration, implementation and selection. The software development method uses the Waterfall Model. Software testing is done through black box testing. Data collection techniques in research using observation and literature study. With this system, it can make it easy for the new student registration committee to process data, make decisions, and support the community. Prospective students can simply access the registration system application in the form of a computerized web site. This is a good solution to solve problems so that an effective and efficient system is created. In conclusion, this High School Student Registration Information System has been completed using PHP and MySQL. Keyword: Information System ,Submission, Website In the current millennial era, information technology is advancing rapidly and in diversity. The advent of the internet will greatly facilitate learning new things without space and time. Computers are equipment designed to meet human needs. In this case, the admission of new students is carried out on the problems carried out by each educational institution / institution in accepting prospective students in the new school year, where so far there are still institutions that have a manual registration system starting from registration, implementation and selection. The software development method uses the Waterfall Model. Software testing is done through black box testing. Data collection techniques in research using observation and literature study. With this system, it can make it easy for the new student registration committee to process data, make decisions, and support the community. Prospective students can simply access the registration system application in the form of a computerized web site. This is a good solution to solve problems so that an effective and efficient system is created. In conclusion, this High School Student Registration Information System has been completed using PHP and MySQL. Keyword: Information System ,Submission, Website